Katsayı Diyagram Yöntemi Ve Uygulamaları - Avşar, Selman Fatih (Fen Bilimleri Enstitüsü)
Klasik kontrol ve modern kontrol teorileri kontrol sistem tasarımında sıklıkla kullanılan yöntemlerdir ancak bunların dışında bir üçüncü kontrol sistem tasarım yöntemi de cebirsel yaklaşımdır. Cebirsel yaklaşım, klasik kontrol ile modern kontrol arasındadır. Polinomsal gösterim kullandığı için sıklıkla polinomsal yaklaşım olarak da isimlendirilir. Bu gösterimde transfer fonksiyonunun payı ve paydası birbirinden bağımsız olarak düşünülür. Lineer cebirsel kontrol tasarım yöntemleri olarak isimlendirilen ve polinomsal gösterimi kullanan bu yöntemler, 1980’lerde ortaya çıkan gözlenebilir ve kontrol edilebilir durum uzayı kanonik formuna denktir. En önemli özellikleri, klasik ve modern kontrol teorilerinin avantajlarını birleştirmesidir. Bu yöntemler arasında en çok kullanılanlardan ve en iyi sonuç verenlerden biri Shunji Manabe tarafından ortaya atılmış Katsayı Diyagram Yöntemidir. KDY, geçmiş fikir ve tecrübelerden yararlanılarak klasik ve modern kontrol teorilerinin avantajlarının uygun bir şekilde bir araya getirilmesi sonucunda elde edilmiş bir kontrol sistem tasarım yöntemidir. İyi kontrol, kontrolcüden beklenenle kontrol edilen arasındaki uzlaşmanın sonucunda elde edilir. Başka bir deyişle iyi kontrol; ne yapılmalıyla, ne yapılabilir arasındaki uzlaşmadır. Klasik kontrol bu uzlaşmanın ne yapılabilir tarafına daha yakınken, modern kontrol bu uzlaşmanın ne yapılmalı tarafına daha yakındır. Uzlaşma, kontrol sistem tasarımında önemli olduğu için tasarım aşamasına uzlaşmayı kolaylaştıracak mekanizmalar yerleştirilmesi gerekmiştir. İnsanoğlunun grafiksel olarak açıklanmış bir problemde oldukça yüksek uzlaşma kabiliyeti vardır. Grafiksel yöntem uzlaşma için bir anahtardır. KDY’deki Katsayı Diyagramı (KD) iyi uzlaşmanın alt yapısını hazırlamaktadır. KD, kontrol sistem tasarımının üç ana unsuru olan kararlılık, cevap hızı ve dayanıklılık özelliklerini tek bir diyagram üzerinde gösterir ve bu da tasarımcının kontrol sistemine tam olarak hakim olmasını sağlar. KD, kontrol sistem tasarımının üç ana unsuru arasında uzlaşma sağlamayı oldukça kolaylaştırmakta ve bu da KDY’nin kontrol sistem tasarımındaki gücünün temel kaynağını oluşturmaktadır. KDY, etkili bir kontrolcü tasarım yöntemidir ancak etkin bir şekilde kullanımı için bilgisayar programına ihtiyaç duyulmaktadır. Bu ihtiyacı karşılamak üzere 2000’li yıllarda çeşitli çalışmalar yapılmıştır. Bu çalışmalara rağmen, Manabe 2002 yılında iyi bir KDY programına şiddetle ihtiyaç olduğunu belirtmiş ve bu çalışmaların geliştirilmesi gerektiğini ifade etmiştir. Bu tarihten sonra, bu konuda birkaç çalışma daha yapılmıştır. Bunlardan biri Manabe’nin kendi sitesinde yayınladığı Matlab tabanlı CDMCAD yazılımı, diğeri ise Köksal ve Hamamcı’nın tasarladığı Matlab tabanlı bir kullanıcı arayüzüdür. CDMCAD, bir arayüz içermemektedir. Bir klasör içinde birçok m-file bulunmaktadır ve ihtiyaca göre çeşitli m-file’ların kullanımı gerekmektedir. Bir arayüz olmadığı için fonksiyonların kullanımını ve hangisinin nerede kullanılacağını öğrenmek ekstra bir emek harcamayı gerektirmektedir. Hamamcı’nın tasarladığı kullanıcı arayüzü ise etkileşimli bir arayüz değildir. KDY kontrölörlerini bulmaktadır ancak kullanıcıya derinlemesine analiz yapma imkanı tanımamaktadır. Bu tez çalışması kapsamında ‘CDM Matlab Tool’ şeklinde isimlendirilmiş kullanıcı dostu bir arayüz geliştirilmiştir. Bu arayüz, KDY’nin etkin ve hızlı bir şekilde kullanımı için tasarlanmıştır ve KDY kontrolcülerini bulmasının yanı sıra kullanıcının çok çeşitli analizler yapmasına da olanak tanır. Tasarım aşamasında akla gelebilecek sorulara cevap verilmeye çalışılmıştır. Arayüz kullanım esnasında kullanıcıya yol gösterecek birçok bildirim ve uyarılarla donatılmıştır. Bu arayüz KDY’nin etkin bir şekilde kullanımının yanı sıra, KDY’yi öğrenmek isteyenler için de oldukça öğretici bir araç olarak kullanılabilir. KDY standart blok diyagramının fiziksel uygulamalarda kullanımı, geri beslemeye türev elamanı ekleyebileceği için, çeşitli sorunlara neden olabilmektedir. Bu yüzden, fiziksel uygulamalarda kullanılmak üzere KDY standart blok diyagramına eş bir blok diyagramı önerilmiştir ancak bu blok diyagramı kullanıldığında tasarlanan bazı KDY kontrolcüleri için sistem iç kararsız olmaktadır. Bu tez kapsamında, böyle bir durumda sistemin iç kararsız olmasını engelleyecek KDY-P olarak adlandırılmış bir yöntem önerilmiştir. Bir kontrol sistem tasarım yönteminin, sadece simülasyonlarda değil fiziksel uygulamalarda da başarılı sonuçlar verdiğini göstermek oldukça önemlidir. Bu tez kapsamında, KDY ile BLDC motor (fırçasız dc motor) kontrolü yapılmış ve KDY’nin hem simülasyonlarda hem de fiziksel uygulamalarda başarılı sonuçlar veren bir yöntem olduğu gösterilmiştir.

Linear algebraic approach lies between the classical and the modern control approaches. It is the third type of control system design technique. Since polynomials are used for system representation in the linear algebraic approach it is also called as polynomial approach. In this representation, numerator and denominator of the transfer function of the plant are considered as independent polynomials. Linear algebraic control methods are equivalent to observable and controllable state space canonic form which came out in 1980s. The most important property of these methods is to merge advantages of both classical and modern control theories. Among these polynomial methods, Coefficient Diagram Method (CDM) proposed by Shunji Manabe is one of the most used methods and gives best results. CDM is a control system design method that is obtained by combining advantages of classical and modern control theories by benefiting from past experiences and ideas. CDM is a rather effective control design method and its design procedure is easier compared to most of the other control techniques. The basic philosophy of CDM has been known in industry and control community for more than 40 years and there are many successful applications of the method. Additionally, the method has been adapted to MIMO systems, digital systems and nonlinear systems recently. Actually, control system design of all liner time invariant systems (LTI) is carried out by selecting proper characteristic polynomial and numerator polynomial which produce the desired relation between input and output. If these polynomials are selected appropriately, controller can be reduced to simple mathematics. It is not too difficult of the selection of the characteristic equation for the design based on only stability and time domain specification; however, when robustness, the third parameter, is included the situation becomes complicated. CDM is a control design method that is developed to solve this type problem. Good control is achieved by setting up a good balance (compromise) between objectives and controlled system response. While the philosophy of classical control is closer to “what can be done”, the philosophy of modern control is closer to “what should be done . Because compromise is important in control system design, mechanisms which will be used for better compromise during design should be established. Humankind has a high compromising capability in problems explained graphically. Graphics can be a key to achieve the compromise appropriately. Coefficient Diagram (CD) which explains problem graphically is used for a better compromise in CDM. CD shows stability, response speed and robustness property of control system in one diagram which therefore provides the control system designer a full awareness. CD makes the compromise between three components of control system design easier and this is one of the main sources of power of CDM. While the transfer function representation, which is easy to understand, is used for system representation in classical control, state space representation, which is more complicated in comparison with transfer functions, is used in modern control. On the other hand, transfer function representation can be inaccurate at pole-zero cancellation case because of its uncontrollable and unobservable structure but there is no such situation in state space representation. Outward approach is used in classical control. According to this strategy, firstly controller structure is determined as parametrically then these parameters adjusted to satisfy the design requirements. Selection of controller structure at the beginning and characteristic polynomials are being limited are the problems in this approach. If the controller structure is not selected appropriately, convenient characteristic polynomial and thus desired specification cannot be satisfied. Even if the design is completed, there is always a hesitation about the optimality of the controller. Inward approach is used in classical control. According to this strategy, control system is designed in order to satisfy the desired closed loop response. Controller parameters are obtained by solving Riccati like equations which are difficult and time consuming to solve. Although the closed loop response is guaranteed in inward approach, robustness and simplicity of the controller is not guaranteed. While classical control has tools which provide intuitive design like bode, nyquist and root locus, there are no such tools in modern control. Polynomial representation which is easy to be understood like transfer function is used in CDM. Polynomial representation is also accurate against pole-zero cancellation. The relation between characteristic polynomial and controller is described by Diophantine equation which is easy to solve, and CD. The relation is expressed mathematically and graphically in a very efficient way and that allows simultaneous design of controller and characteristic polynomial. At first, characteristic polynomial and controller are determined partly and remaining parameters are determined during the design. This approach is called simultaneous design approach. Simple and robust controllers which achieve desired specification are easily designed through this feature provided by CDM. In addition to this, CD, graphical tool of CDM, provides intuitive design like bode and nyquist in classical control. By using CDM, design specifications are obtained with a good compromise between stability, response and robustness. CDM is an efficient controller design method but computer aid is needed for an efficient usage. Some studies have been done to meet this need in 2000s. Despite of these studies, Manabe expresses to strong need of a CDM CAD tool. There has not been announced a tool meets these needs and provide detailed research since that time. A user-friendly and interactive GUI named ‘CDM Matlab Tool’ was designed in this thesis scope. This tool was designed for fast, accurate and efficient usage of CDM. In addition to finding CDM controllers, it provides user capabilities doing more detailed analysis. Tool can be used for getting an answer to questions appears in design stage. The GUI is equipped with lots of notifications and warnings in order to provide user an easier usage. This tool can be used for not only efficient usage of CDM but, also as an educational tool. Standard block diagram of CDM has some drawbacks in physical applications due to the derivative component on the feedback line. To solve this problem, a new block diagram was proposed in the literature. Unfortunately, when this block diagram is used, closed-loop system can be unstable for some applications. In the scope of this thesis, a new approach named CDM-P to solve this problem is proposed. It is important for a method in control system design that it is successful not only simulations but also in practical applications. In the scope of this thesis, BLDC motor (brushless DC motor) was controlled with CDM controllers. It is shown that CDM is a successful control system design method for both simulations and practical applications.
Coefficient Diagram Method And Its Applications
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2012
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2012
Keywords: katsayı diyagram yöntemi; kdy; fırçasız dc motor; grafiksel kullanıcı arayüzü; coefficient diagram method; cdm; brushless dc motor; graphical user interface